2004
DOI: 10.21236/ada422173
|View full text |Cite
|
Sign up to set email alerts
|

Advanced UXO Detection/Discrimination Technology Demonstration - Kaho'olawe Hawaii

Abstract: ABSTRACT:The primary technical objective of this demonstration project was to evaluate the detection and discrimination capabilities (including production rates and costs) of advanced UXO systems in difficult magnetic clutter environments such as those encountered at Kaho'olawe, Hawaii. One 90-m by 111.1-m (1-hectare) area and 10 (not necessarily contiguous) 30-m by 30-m test grids within the Kaho'olawe Quality Assurance (QA) Range were prepared to present a limited range of target/clutter/ topography/vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Geophysical data were collected on the island of Kaho'olawe, Hawaii as part of an Environmental Security Technology Certification Program (ESTCP) project to determine the effectiveness of EMI sensors fielded in areas with a large background geologic response (Cargile et al, 2004). Ordnance and ordnance related scrap were emplaced in a number of test plots.…”
Section: Processing Of Data Collected On Kaho'olawe Island Hawaiimentioning
confidence: 99%
“…Geophysical data were collected on the island of Kaho'olawe, Hawaii as part of an Environmental Security Technology Certification Program (ESTCP) project to determine the effectiveness of EMI sensors fielded in areas with a large background geologic response (Cargile et al, 2004). Ordnance and ordnance related scrap were emplaced in a number of test plots.…”
Section: Processing Of Data Collected On Kaho'olawe Island Hawaiimentioning
confidence: 99%
“…Remediation efforts conducted on the Island of Kaho'olawe, Hawaii, encountered VRM in the soils when EMI and magnetic geophysical methods were employed to aid in the detection of UXO. Cargile et al (2004) reports that 61,261 anomalies were dug at the Kaho'olawe site, where approximately 70% of the anomalies were caused by non-hazardous metal objects and 27% were caused by geology. This high percentage of geological anomalies illustrates the importance of developing an understanding of the influence of magnetic soils on EMI data in UXO detection.…”
Section: Introductionmentioning
confidence: 99%
“…During the Kaho'olawe cleanup operations the UXO contractor conducted "'EM and Flag' surveys using the EM-61 and the TM-5 EMU in a real-time detection/discrimination mode" (Cargile et al, 2004). During surveying, they "detected 61,261 subsurface anomalies and, after digging, they have found that only 2.7 percent are UXO, 27 percent are false positives from geologic sources, and 70.3 percent are the result of buried metal from both UXO and non-UXO related materials" (Cargile et al, 2004). It would seem that a significant reduction in digging clutter could be achieved through the use of digital geophysics and discrimination.…”
Section: Introductionmentioning
confidence: 99%